Implicit theories of emotional intelligence, ability and trait-emotional intelligence and academic achievement - Costa, Ana (Array, 2020)
This study examines the effect of the implicit theories of emotional intelligence and of emotional intelligence (EI; ability and trait EI) on students’ academic achievement (GPA). Five hundred twenty-three 10th graders (Mage = 15.5; SD = 0.67) completed measures of implicit theories (IT) and EI (performance and self-report). The results confirmed the direct effect of EI (ability and trait EI) on students’ GPA. Moreover, implicit theories of EI affected students’ trait EI and only indirectly affected students’ achievement. Multigroup analyses indicated that the IT and EI effects on students’ GPA were similar across students’ gender and socio-professional status. These findings underline the relevance of students’ implicit theories and EI and suggest their usefulness as strategies to foster academic success.